Association of the rs17782313, rs17773430 and rs34114122 Polymorphisms of/near MC4R Gene with Obesity-Related Biomarkers in a Spanish Pediatric Cohort - Joaquín Carrasco-Luna; María Navarro-Solera; Marie Gombert; Vanessa Martín-Carbonell; Álvaro Carrasco-García; Cristina Del Castillo-Villaescusa; Miguel Ángel García-Pérez; Pilar Codoñer-Franch (MDPI AG, 2023)
Obesity is a multifactorial disease whose onset and development are shaped by the individual genetic background. The melanocortin 4 receptor gene (MC4R) is involved in the regulation of food intake and energy expenditure. Some of the single nucleotide polymorphisms (SNPs) of this gene are related to obesity and metabolic risk factors. The present study was undertaken to assess the relationship between three polymorphism SNPs, namely, rs17782313, rs17773430 and rs34114122, and obesity and metabolic risk factors. One hundred seventy-eight children with obesity aged between 7 and 16 years were studied to determine anthropometric variables and biochemical and inflammatory parameters. Our results highlight that metabolic risk factors, especially alterations in carbohydrate metabolism, were related to rs17782313. The presence of the minor C allele in the three variants (C-C-C) was significantly associated with anthropometric measures indicative of obesity, such as the body mass and fat mass indexes, and increased the values of insulinemia to 21.91 µIU/mL with respect to the wild type values. Our study suggests that the C-C-C haplotype of the SNPs rs17782313, rs17773430 and rs34114122 of the MC4R gene potentiates metabolic risk factors at early ages in children with obesity.